Specific dysregulation of inflammatory and anti-inflammatory cytokine responses in pregnant women with COVID-19 infections - Manggala Pasca Wardhana; Erry Gumilar Dachlan; Kuntaman Kuntaman; Budi Utomo; Ifan Ali Wafa; Salsabila Nabilah Rifdah; Dharma Putra Perjuangan Banjarnahor; Ario Danianto (GarVal Editorial Ltda., 2023)
Context: Owing to its extensive inflammation, COVID-19 infection may have a specific response in the anti-inflammatory milieu of pregnancy. Aims: To analyze the lacking evidence of systemic inflammatory and anti-inflammatory cytokine responses of pregnant women with COVID-19 infection compared to normal pregnancies. Methods: This case-control study was performed on third-trimester symptomatic COVID-19 pregnant women compared with normal pregnancies without other significant inflammation risks. A between-group analysis was conducted to assess the inflammatory, and anti-inflammatory cytokines and chemokines. Through a comparison and correlation analysis, we detected differences between cytokines in the COVID-19 group based on the severity of the infection. Results: Pregnant women with COVID-19 had higher procalcitonin levels (p<0.01), IL-6 (p=0.05), TNF-a, IFN-γ/IL-4 ratio (p<0.01), and lower IL-4 (p<0.05), implying a higher proinflammatory cytokine imbalance in this group compared with normal pregnancies. White blood cells (p<0.05; r=0.345), and IL-17 (p<0.05; r=0.328) had weak positive correlation, while CRP (p<0.01; r=0.484), and IL-6 (p<0.01; r=0.41), had moderate positive correlation with COVID-19 severity during pregnancy. Conclusions: COVID-19 infections provide a unique non-dominance of the anti-inflammatory response in pregnant women, as indicated by a lower response of Th2, which may counteract the Th1 response. These cytokine dysregulations may disturb the viral defense mechanism, leading to a proinflammatory condition as shown by higher TNF-a, IL-6, and IFN-g/IL-4 ratios. Some inflammatory markers have a positive correlation with COVID-19 severity (WBC, CRP, IL-6, and IL-17), suggesting their potential roles as severity markers during pregnancy.